Respectability, morality and reputation: social representations of intimate partner violence against women in Cape Town - Van Niekerk, Taryn Jill (2015)
Includes bibliographical referencesThis study examined the social representations of intimate partner violence (IPV) that emerged amongst violent men, their social networks and within the media, and framed within social representations theory and feminist poststructuralism. In-depth individual interviews were conducted with 11 men, recruited from two men's programmes at an NGO, and seven focus group discussions were conducted with the men's social networks. A total of 11 3 reports on violence against women were collected from two newspapers that draw the largest readership in the Cape Town area. A thematic decomposition analysis - emphasising language, power and subjectivity - revealed how participants' representations of respectability, morality, and reputation served to maintain patriarchy, and make violence permissible. The findings also shed light on the polarity of human thought, demonstrating how 'non-valid' victims of IPV are blamed and 'othered' for the violence perpetrated against them; yet in contrast, men who perpetrate violence are protected and defended. Understanding violence as an intersectional experience - defined by race, class, gender and sexuality in the context of post-apartheid South Africa - is central to the analysis. This study employed an integrated and unique methodology to sample men, their networks and printed media reports, which involved an analysis of violence as a social act. To my knowledge, it is the first study to have asked questions about what social representations of intimate partner violence emerge in men and their social networks' narratives and how these resonate in South African media's discourses. Suggestions for prevention and community-based programmes, interventions for perpetrators and victims of intimate partner violence, and practical recommendations for improved journalistic practice are provided. The community, relationships and individuals are shown to be inseparable spheres, and the contextualised analyses of power and oppression are shown to open possibilities for social change